Usual Interstitial Pneumonia in Contemporary Surgical Pathology Practice: Impact of International Consensus Guidelines for Idiopathic Pulmonary Fibrosis on Pathologists. - Eldersveld, Jordan M.; Eunhee S. Yi; Kunze, Katie L.; Smith, Maxwell L.; Tazelaar, Henry D.; Larsen, Brandon T. (Archives of Pathology & Laboratory Medicine, 2021)
* Context.--Idiopathic pulmonary fibrosis is a clinical syndrome characterized by the presence of usual interstitial pneumonia (UIP) radiologically and pathologically. Per consensus criteria adopted in 2011, diagnosis of idiopathic pulmonary fibrosis no longer requires a biopsy in an appropriate context if UIP is seen on imaging. As a result, lung biopsies are now typically reserved for patients having indeterminate clinical or imaging findings or suspicion for alternative diagnoses, but the impact of updated guidelines on pathology practice remains unclear. Objective.--To determine the frequency of histologic UIP before and after 2011. Design.--Surgical lung biopsies from adults were studied within two 4-year periods: July 1, 2006 through June 30, 2010 and January 1, 2012 through December 31, 2015. Pathology slides were reviewed in a fashion blinded to clinical information and were classified using current guidelines. Results.--Biopsies from 177 and 86 patients (mean [SD] age, 62 [12] and 59 [14] years; 50.3% [89 of 177] and 48.8% [42 of 86] men) before and after 2011, respectively, were reviewed. Probable UIP or UIP was less-frequently encountered after 2011 in all patients with fibrosis (9 of 54 [16.7%] versus 41 of 119 [34.5%] before 2011, P = .02) and also in patients 50 years old and older (8 of 46 [17.4%] versus 39 of 109 [35.8%] before 2011, P = .02), with a concomitant rise in cases indeterminate for UIP or showing alternative diagnoses. Conclusions.--Histology for UIP is less frequently encountered in our contemporary practice compared with the historic era. The pretest probability of a non-UIP diagnosis is now high, even in elderly patients, underscoring the need for pathologists to be familiar with the histologic features of alternative diagnoses.